(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2022)
In this paper we studied the characteristics of the response when different boundary conditions are applied. We analyzed a two-dimensional model of the ground-foundation system (construction) and investigated how the physical-mechanical characteristics (density and propagation velocity) of the constituent elements of the ground-foundation system affect the energy that will enter the building.